2002
DOI: 10.1093/embo-reports/kvf025
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of mRNAs targeted to yeast mitochondria

Abstract: It is agreed that nuclear-encoded mitochondrial proteins are post-translationally targeted to mitochondria, even if, in some cases, a co-translational phase can assist the import of precursor proteins. We used yeast DNA microarrays to analyse the mRNA populations associated with free and mitochondrion-bound polysomes. As expected, many mRNAs, known to encode mitochondrial proteins, are localized to free cytoplasmic polysomes, but many are localized to mitochondrion-bound polysomes. Furthermore, the 3′-UTR of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
287
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(308 citation statements)
references
References 35 publications
13
287
0
4
Order By: Relevance
“…As expected, the Atp1 p.m.RNA was found to be associated with mitochondria to an extent of up to 45%. This value is in agreement with the previously reported one (Marc et al 2002) and reflects the fact that a portion of mitochondria-bound polysomes were released during mitochondria isolation. Up to 35% of the preMsk1 p.m.RNA was found to be mitochondriaassociated, which is comparable to the Atp1 p.m.RNA.…”
Section: The Soluble Pool Of Eno2p Is Required For Trk1 Importsupporting
confidence: 93%
See 2 more Smart Citations
“…As expected, the Atp1 p.m.RNA was found to be associated with mitochondria to an extent of up to 45%. This value is in agreement with the previously reported one (Marc et al 2002) and reflects the fact that a portion of mitochondria-bound polysomes were released during mitochondria isolation. Up to 35% of the preMsk1 p.m.RNA was found to be mitochondriaassociated, which is comparable to the Atp1 p.m.RNA.…”
Section: The Soluble Pool Of Eno2p Is Required For Trk1 Importsupporting
confidence: 93%
“…It has been shown that the mRNAs of numerous mitochondrially addressed proteins are translated in the vicinity of the mitochondria to facilitate their compartmentalization (Marc et al 2002). This may also be the case for preMsk1p, which is essential for mitochondrial translocation of tRK1.…”
Section: The Soluble Pool Of Eno2p Is Required For Trk1 Importmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, mammalian mitochondria appear to possess specific receptors for binding ribosomes [49]. Genes of ancient bacterial origin comprise a significant proportion of these mitochondrion-associated mRNAs, while genes of eukaryotic origin that encode organellar proteins generally contain presequences and seem to be primarily translated on cytoplasmic polysomes [50]. The ribosomal recruitment of mRNAs requires specific features of the 3′ untranslated region of the transcripts [51].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In general, these strategies seem to reinforce targeting information present within the protein products themselves. In S. cerevisiae, for example, nuclearly coded mRNAs for several mitochondrial proteins bearing mitochondrial import signals seem to be translated preferentially by cytoplasmic ribosomes tightly associated with the organelles, facilitating their localization (Marc et al, 2002). This targeting is dependent upon signals in the mRNA 3Ј-untranslated regions.…”
Section: Introductionmentioning
confidence: 99%